Evaluation of an enzyme-linked immunosorbent assay (ELISA) using phenolic glycolipid (PGL) and crude antigens for screening of sera of cattle infected with Mycobacterium bovis - SUJITNAYAK, SUJITNAYAK; VERMA, RISHENDRA; JOSHI, BEENU; VENKATESAN, K (The Indian Journal of Animal Sciences, 2014)
Enzyme-linked immunosorbent assay (ELISA) was used to screen sera of cattle infected with M.bovis using PPD, heat killed sonicated antigens and species-specificM.bovis phenolic glycolipid (PGL) antigen Ninty cattle sera (50 tuberculin positive, 30 tuberculin negative, 5 tuberculin doubtful and 5 tuberculous cattle) were investigated. With PPD, heat-killed sonicated and deacylated PGL antigens, 78%, 71 % and 35.5% sera were positive. Out of these 90 sera, 21,20 and 18 sera from tuberculm reactor cattle that tested positive with PPD, heat killed sonicated and PGL antigens, were titrated for IgG levels by ELISA Llsing the above 3 antigens. Three sera with each of the 3 antigens showed a titre range of 1280 to 2560; 19 positive sera (5 from PPD, 7 from heat killed sonicated antigen and 7 from PGL antigen) showed titre range between 640-1280; and 28 (11 from PPD, 9 from heat killed sonicated and 8 from PGL antigen) sera fell in titre range of 320 to 640. The minimum IgG titre ranged from 169 to 320 in 3 sera (2 PPD and 1 heat killed sonicated tested sera). Results suggested to do more work with 3 antigens so as to elucidate role of ELISA as an adjunct test.